Relative expression of ALPP gene in lung cancer induced by gelam honey by quantitative reverse transcription polymerase chain reaction / Siti Norfazila A. Wahab - A. Wahab, Siti Norfazila (2014)
Honeys have been proven to have an anti-oxidant and antitumor properties and Gelam honey was confirmed to have an ability of suppressing colon cancer cell growth. However, there are not many scientific studies that have been conducted to investigate the antitumor effects of Malaysian Gelam honey on lung cancer cells. ALPP gene code for alkaline phosphatase, which function in the regulation of phosphorylation, where phosphorylation play important and significant role in regulating the function of tumor suppressor protein, p53.The study is an initial attempt to investigate the relative expression of ALPP gene in lung cancer cell upon treatment with Gelam honey by using real time reverse transcription polymerase chain reaction. For the gene expression, the total RNA which is extracted from the untreated and treated lung cancer cell was reverse transcripted into cDNA and amplified with qRTPCR. The relative quantification of gene expression is calculated using Delta-delta Ct method. The result of this study revealed that the expression ALPP gene in treated lung cancer cell with Gelam honey is up regulated. From the normalization of gene expression using 2-△△Ct method, the ALPP gene is increased by 14.42 folds in the lung cancer cell which was treated with Gelam honey. Hence it can be concluded that ALPP gene showed different expression when treated with Gelam honey, where it is up-regulated. This up-regulation of ALPP gene showed that Gelam honey possessed therapeutic effect on lung cancer as up-regulation of ALPP gene will inhibit the growth of lung cancer cell by activated the p53 tumor suppressor protein.